Meanings in Men’s Classic Shoes - Gomes Lacerda Cavalcante Abraão; Gomes de Medeiros, Wellington (DAT Journal, 2021)
This paper presents research on the interpretations of two age groups of men about classic male shoes. It describes the meanings associated with the products according to the pragmatic and emotional dimensions. The methodology included data gathering in two phases with questionnaires and interviews with 122 people. In the first phase, the meanings were classified according to the Meaningful Interaction model. In the second phase, correlations were established between the meanings and the tangible and visual attributes of the product. Ten models of shoes were displayed to the respondents. The results of Phase 1 identified 171 semantic values: 65% correspond to the emotional dimension, and 35% correspond to the pragmatic dimension. The Phase 2 revealed that the correlations between the meanings and attributes of the products refer mainly to shape, material and color. The study concluded that the meanings in men’s classic shoes arouse more associations related to emotional memory, tradition and cultural values of the respondents than the pragmatic qualities of the products